First Example of Aryl–Hetaryl Cross-Coupling via [5,5]-Sigmatropic Rearrangement - Buravov, Oleksandr V.; Tomak, Victor O.; Shishkina, Svitlana V.; Chebanov, Valentyn A. (Synthesis, 2024)
Polysubstituted furans and thiophenes with orthogonal functional groups were synthesized by a Strecker-type reaction leading to (arylaminonitriles), which underwent a [5,5]-sigmatropic rearrangement under mild conditions. The intramolecular character of the rearrangement was additionally proved.
Keywords: heterocycles; aminonitriles; sigmatropic rearrangement; furans; thiophenes; thiazoles